Bioremediation of Contaminated Soil with Crude Oil Using New Genus and Species of Bacteria - Mohamed Taher, Ahmed (Journal of King Abdulaziz University: Marine Sciences, 2022)
In this study, the ability of bacteria presents in soils contaminated with crude oil to degrade petroleum hydrocarbons at the study sites (Al-Fatha and AL-Qayyarah) is investigated. Ten bacterial isolates are isolated from the soils of the study area, collected from different areas of Al-Fatha near the North Refineries in Salah-Din Governorate and AL-Qayyarah Refinery in Nineveh Governorate. These bacterial isolates show uneven growth in the mineral medium prepared with crude oil. Three new bacterial genera and two species are obtained, one of which belongs to the genus Bacillus and the other to the genus Exiguobacterium. The new bacterial isolates are recorded in the National Center for Biotechnology Information (NCBI) for the first time with the following numbers:(LC596402, LC596403& LC596406) for the genus (AM-I-1, AM-I- 2, and AM-I-5), respectively and (LC596404, LC596405) for the species (AM-I-3 and AM-I-4), respectively. The results show the ability of the isolates (AM-I-1, AM-I-2, AM-I-3, AM-I-4, and AM-I-5) to consume Polyaromatic Hydrocarbons (PAHs) compounds in the mineral medium prepared with crude oil with different concentrations and degrees, temperatures and pH conditions. The optimum conditions are pH 7, temperature 40°C and 2% crude oil concentration with a period of 12 days. The bacteria (AM-I-3) has outperformed the rest of the bacterial isolates with a consumption of (PAHs) compounds of 86.5%, followed by bacterial isolates and their mixture with a consumption rate of (84.42%, 78.19%, and 75.20%) (AM-I-1, AM-I-4, & mix of isolates), respectively.